The Effect of Monetary Rewards on the Performance of Employees in an Organisation: A Case Study of Kabale District Local Government. - Nayebare, Gaston (Kabale University, 2023)
The study examined the impact of monetary rewards on employee productivity, a case study of Kabale district local government. The study was guided by objectives like finding out the effect of monetary rewards on employee productivity in Kabale district, to identify the effects of salaries and wages on employee productivity in the Kabale district, and assessing the factors affecting employee productivity in the Kabale district. The study used a descriptive research design. The study population was 31 employees of the organization. The population of this study comprised of all the employees under the finance department, CAO's office and human resource department at the district. The study used interview guides, questionnaires and documentary as the methods of data collection. The study finds out that employee needs and wants as the most commonly effect of monetary rewards on employee productivity in Kabale district local government as an organization. Wages and salaries rewards are an effective tool in motivating workers and consequently increase their performance. Also, employee productivity is affected by empowerment in a way that when an employee is empowered will perform better than the one who is not empowered and it also improves employee morale. The study thus concludes that there are obvious relations between monetary rewards and employee's performance; fringe benefit can stimulate employees' performance. Though, some of the major goals of training employees contain, increase in production, lesser labor turnover rate, higher confidence and better management and training facilitates to decrease cost as it enhances productivity, and promotes objective congruency. Lack of training raises rate of absenteeism, low productivity, bad quality and refuses and results in high unit cost. This study recommends that the management in the Kabale district local government and all other organizations evaluates the reward systems that are currently in place as well as the kind of influence they have on employee performance. This would help them understand the issues surrounding administration and the corresponding influence of non-monetary rewards towards employee performance. They would make a significant contribution towards their improvement of reward strategies in order to enhance their competitive edge.